Atividade citotóxica de secretoma de Aspergillus fumigatus em células de carcinoma de pulmão - Sousa, Ana Cristina Peres de [UNIFESP] (2017)
Introduction Aspergillus fumigatus is a fungi with high adaptive capacity and virulence factors that favors its establishment and colonization in the human host. Species of Aspergillus genus are recognized for its high capacity for production of secondary metabolites, extensively documented in the literature. Among these metabolites, there are some isolated molecules used as drugs, for the cholesterol control (lovastatin) and even in the combat of other fungi (echinocandins). Several molecules produced by A. fumigatus have already been tested on human cells/ in vitro cells searching for bioactive molecules. Gliotoxin is one of the most studied A. fumigatus molecule, that inhibits the host immune response, negatively modulating angiogenesis and inducing many cell lines to apoptosis. In view of the great diversity of molecules produced by A. fumigatus, the interest to explore its biological potential focusing on cytotoxic activity in lung carcinoma cells, the target organ of infection by this agent in the human host is justified. Objective To obtain the secretome from clinical isolates of A. fumigatus and investigate the potential cytotoxic activity of its fractions on A549 cells. Methodology Six clinical isolates of A. fumigatus from patients with pulmonary aspergillosis were identified at species level using a polyphasic approach, including ITS region, Calmodulin and β-tubulin genes sequencing. After standardization of the optimal conditions to obtain secretomes samples with reproducible composition (same profile when evaluated by LC-MS), we started the screening for biological activity of these molecules in A549 cells through cytotoxicity assays in which measurement of metabolic activity was done by the 3-(4,5-dimethylthiazol-2yl)-2,5-diphenyltetrazolium bromide salt (MTT) assay. Once that the most active secretome was identified, it was submitted to sequential fractionations through preparative Liquid Chromatography (LC), with the aim of purifying the fraction that was responsible for the cytotoxic effect found. Finally, annexin V cell death assays were performed to analyse the cell death pattern induced by the active subfraction. Result The standardization of A549 cell culture and secretome extraction in MMBA culture medium of reproducible composition was successfully achieved. Regarding the biological activity of secretome samples from 6 A. fumigatus isolates, the isolate 934 was presented the highest cytotoxic effect in MTT assays. From this finding, 2 sequential secretome fractionations were performed and it was possible to isolate a subfraction identified as Z5, which presented consistent cytotoxic activity, reducing 90% of cell viability when compared to control (p <0.02). The annexin V assay has led to the conclusion that this subfraction mainly induces apoptosis in A549 cells. New assays are needed to characterize the A. fumigatus secretome subfraction that presented cytotoxic activity as well as to confirm its potential antitumor activity.